Combining knowledge discovery, ontologies, annotations, and semantic wikis - Astudillo, Hernán (2009)
Semantic Wikis provide an original and operational infrastructure for efficiently com- bining semantic technologies and collaborative design activities. This text presents: a running example and its context (organization of the collections in a museum); concepts of wikis as a tool to allow computer supported cooperative work (cscw); concepts of se- mantic technologies and knowledge representation; concepts and examples of semantic wikis; anatomy of a semantic wiki (reasoning tools, storage, querying); and research directions.